Luxury chocolate: Is scarcer better? Retail shelf-displays and perceived scarcity - Hatton-Jones, Siobhan (2015)
Consumers within retail settings are more likely to infer that scarcer products are of higher quality and therefore more likely to choose them (Lynn 1989). As a result product scarcity coupled with shelf display organisation (shelf based scarcity) influence how consumers’ process product information; which in turns alters their preference. Contamination Theory underpins the entire study, and varying shelf based scarcity is used a background variable to ascertain the differing effects on perception of luxury. Perception of luxury is the tested to investigate if this variable moderates the established relationship between perception of luxury, product evaluation and purchase intention. Methodological significance is added through the use of factorial design to simultaneously study shelf organisation and degrees of product scarcity, adding ecological validity with embedded stimulus and real life brand. The theoretical significance of this study is to add to the diminutive knowledge available surrounding scarcity, its application in luxury retail settings and retail context of contamination theory. Specifically, for practitioners, whether there is as optimal level of scarcity that may induce perceptions of luxury and increase product evaluation and purchase intention; as luxury management are under strain my marketing on the fragile perception of scarcity.